2022
DOI: 10.30541/v50i3pp.219-244
|View full text |Cite
|
Sign up to set email alerts
|

The Utilisation of Education and Skills: Incidence and Determinants among Pakistani Graduates

Abstract: This study estimates the incidence of job mismatch and its determinants in Pakistan, based on three categories: (i) qualification mismatch, (i) skill mismatch, and (iii) field-of-study mismatch. It uses both primary and secondary datasets that target graduates employed by the formal sector. The study measures the qualification mismatch using three approaches and finds that about one third of the graduates sampled face a qualification mismatch. Similarly, more than one fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…However, as the findings apply to PhD graduates in a science, mathematics or engineering field, these results cannot be generalized. Other studies provide evidence that females are more likely to be mismatched as opposed to their male counterparts (Hensen et al ., ; Farooq, ). For men, mismatch is more likely to be the result of career‐oriented reasons like pay and promotion opportunities, or changing career interests, whilst women are more likely to report mismatch due to family‐related reasons, the job location or working conditions (Robst, ; Bender and Heywood, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the findings apply to PhD graduates in a science, mathematics or engineering field, these results cannot be generalized. Other studies provide evidence that females are more likely to be mismatched as opposed to their male counterparts (Hensen et al ., ; Farooq, ). For men, mismatch is more likely to be the result of career‐oriented reasons like pay and promotion opportunities, or changing career interests, whilst women are more likely to report mismatch due to family‐related reasons, the job location or working conditions (Robst, ; Bender and Heywood, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to study programme characteristics, horizontal mismatch is determined by whether students were enrolled in a part‐time or full‐time programme. Several studies found that graduates who studied full‐time are more likely to obtain a job that matches their field compared to graduates who studied part‐time (Farooq, ; Boudarbat and Chernoff, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the WSA approach in SEG dataset, graduates were asked: "In your opinion, how much formal education/qualification (years) and experience (years) is required to perform your current job well?" By comparing the attained education/qualification with required education/qualification, the graduates have been classified into three categories: over-qualified, under-qualified and matched graduates [see Farooq (2011) for detail]. For the third, RM measure, the methodology of Verdugo and Verdugo (1989), and NG (2001) has been followed to measure the required 4 Grade drift is dropped in quality of education.…”
Section: Methodological Framework For the Estimation Of Job Mismatchmentioning
confidence: 99%
“…Islamabad and Rawalpindi to study the job mismatch phenomenon in depth. At a broader level, the targeted universe in the SEG dataset has been divided into three major groups: graduates in the federal government, graduates in the autonomous/semi-autonomous bodies under the federal government and finally graduates in the private sector [see Farooq (2011) for detailed sampling and data collection]. Figure 2 shows the distribution of complete sample of 514 graduates across three major groups according to their relative employment share.…”
Section: Data Descriptionmentioning
confidence: 99%